До питання знаходження орієнтації та поточної позиції об'єкта у просторі на прикладі саматосенсорної перчатки. - Старокожев, С. В.; Свид, І. В. (My University, 2021)
The paper considers the problem of finding the orientation and current position of an object in space using the example of a somatosensory glove. A variant of finding the spatial position of an object is also presented and a variant of visualization in 3D using hardware and software is proposed.
Keywords: MATLAB; фильтр Каллмана; БПЛА